Role of organizational culture, motivation and kaizen to improve employee performance - Pratama, Kemas Evian Bagus; David, Agus; Imron, Ali (Jurnal Mantik, 2024)
This research aims to determine and analyze the moderating role of kaizen culture and the mediating role of work motivation on the performance of employees under the control of the IT Directorate of PT XYZ. This research uses a quantitative method with a saturated population and a sample of 98 employees. The data collection technique uses a questionnaire in the form of a combination of closed answers on an interval scale of 1-10 with the help of an online questionnaire and then analyzed using the SmartPLS 4.0.9.1 program. The research results based on validity and reliability tests show that the data is valid and reliable. Based on direct and indirect hypothesis testing, it was found that (1) organizational culture has a positive and significant effect on work motivation with a sample value of 0.669 and a p-value of 0.000. (2) Work motivation has a positive and significant effect on employee performance with a sample value of 0.323 and a p-value of 0.010. (3) Organizational culture has a positive and significant effect on employee performance with a sample value of 0.342 and a p-value of 0.004. (4) Kaizen culture has a positive and significant effect on employee performance with a sample value of 0.519 and a p-value of 0.000. (5) Kaizen culture moderation in organizational culture does not positively and significantly influence employee performance with a sample value of 0.092 and a p-value of 0.069. (6) positive and significant work motivation mediates organizational culture on employee performance with a sample value of 0.216 and a p value of 0.012.